2018
DOI: 10.1007/s13770-018-0132-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Fetal Cartilage Progenitor Cells During Long-Term Expansion in a Xeno-Free Medium

Abstract: BACKGROUND: Stem cell therapy requires a serum-free and/or chemically-defined medium for commercialization, but it is difficult to find one that supports long-term expansion of cells without compromising their stemness, particularly for novel stem cells. METHODS: In this study, we tested the efficiency of StemPro Ò MSC SFM Xeno Free (SFM-XF), a serum-free medium, for the long-term expansion of human fetal cartilage-derived progenitor cells (hFCPCs) from three donors in comparison to that of the conventional a-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Optimization of this selection process, with major emphasis set on safety and consistency, has led to the identification and recognition of allogenic primary progenitor cell types as highly promising and efficient candidates for cell therapies (De Buys Table 2. Roessingh et al, 2006;Mirmalek-Sani et al, 2006;Grognuz et al, 2016;Kim et al, 2018). Medical needs in the domains of burns and chronic cutaneous wound management are difficult to meet, due to the complex nature of wound bed environments and the delicate process of coordinated responses governing wound closure.…”
Section: Discussionmentioning
confidence: 99%
“…Optimization of this selection process, with major emphasis set on safety and consistency, has led to the identification and recognition of allogenic primary progenitor cell types as highly promising and efficient candidates for cell therapies (De Buys Table 2. Roessingh et al, 2006;Mirmalek-Sani et al, 2006;Grognuz et al, 2016;Kim et al, 2018). Medical needs in the domains of burns and chronic cutaneous wound management are difficult to meet, due to the complex nature of wound bed environments and the delicate process of coordinated responses governing wound closure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the availability of donor tissue is limited, a fetal cartilage yields more than 20-fold the number of cells than the same amount of adult cartilage. In addition, we have also shown that hFCPCs can be expanded for more than 30 passages without losing their proliferation ability in a xeno-free medium, which resulted in approximately 10 30 cells from 5 × 10 5 cells of initial culture 57 . Therefore, we believe hFCPCs have a competitive commercial value, but understand that actual commercialization requires further investigation on their characteristics and behavior during long-term expansion and development of means for mass production and quality control as well.…”
Section: Discussionmentioning
confidence: 89%
“…passages without losing their proliferation ability in a xenofree medium, which resulted in approximately 10 30 cells from 5 Â 10 5 cells of initial culture 57 . Therefore, we believe hFCPCs have a competitive commercial value, but understand that actual commercialization requires further investigation on their characteristics and behavior during long-term expansion and development of means for mass production and quality control as well.…”
Section: Mscs Induction Of Tregs Bymentioning
confidence: 99%
“…Pragmatic optimization of cell source selection and processing is crucial within translational development and clinical implementation of cell therapies and related products. Iterative amelioration and successful application of standardized workflows have led to identify allogenic primary FPC sources as highly promising and efficient candidates for regenerative medicine (Hebda and Dohar, 1999;De Buys Roessingh et al, 2006;Mirmalek-Sani et al, 2006;Ferguson, 2007, 2008;Larijani et al, 2015;Grognuz et al, 2016b;Kim et al, 2018). Upon adequate isolation from fetal tissues (i.e., enzymatic or mechanical methods), culture-expansion and cryopreservation, progeny cells and derivatives present numerous advantages.…”
Section: Allogenic Fpc Technology For Translational Researchmentioning
confidence: 99%